EXILL—a high-efficiency, high-resolution setup for γ-spectroscopy at an intense cold neutron beam facility. (7th November 2017) - Jentschel, M.; Blanc, A.; de France, G.; Köster, U.; Leoni, S.; Mutti, P.; Simpson, G.; Soldner, T.; Ur, C.; Urban, W.; Ahmed, S.; Astier, A.; et al.
Abstract: In the EXILL campaign a highly efficient array of high purity germanium (HPGe) detectors was operated at the cold neutron beam facility PF1B of the Institut Laue-Langevin (ILL) to carry out nuclear structure studies, via measurements of γ -rays following neutron-induced capture and fission reactions. The setup consisted of a collimation system producing a pencil beam with a thermal capture equivalent flux of about 10 8 n s −1 cm −2 at the target position and negligible neutron halo. The target was surrounded by an array of eight to ten anti-Compton shielded EXOGAM Clover detectors, four to six anti-Compton shielded large coaxial GASP detectors and two standard Clover detectors. For a part of the campaign the array was combined with 16 LaBr 3 :(Ce) detectors from the FATIMA collaboration. The detectors were arranged in an array of rhombicuboctahedron geometry, providing the possibility to carry out very precise angular correlation and directional-polarization correlation measurements. The triggerless acquisition system allowed a signal collection rate of up to 6 × 10 5 Hz. The data allowed to set multi-fold coincidences to obtain decay schemes and in combination with the FATIMA array of LaBr 3 :(Ce) detectors to analyze half-lives of excited levels in the pico- to microsecond range. Precise energy and efficiency calibrations of EXILL were performed using standard calibration sources of 133 Ba, 60 Co and 152 Eu as well as data from the reactions 27 Al(n, γ ) 28 Al and 35 Cl ( n, γ) 36 Cl in the energy range from 30 keV up to 10 MeV.